1999
DOI: 10.1191/096120399678847461
|View full text |Cite
|
Sign up to set email alerts
|

Anti-phospholipid antibodies in patients with multiple sclerosis and MS-like illnesses: MS or APS?

Abstract: A substantial number of aPL-positive patients have a concurrent diagnosis of MS or MSL, frequently presenting with elevated IgM aCL, optic neuritis, and transverse myelitis. The anti-phospholipid syndrome (APS) should be strongly considered as an alternative diagnosis to MS in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
41
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(45 citation statements)
references
References 34 publications
3
41
1
Order By: Relevance
“…[5][6][7] There have been some case reports or series linking anticardiolipin antibodies (aCL Ab) and MS, optic neuritis, or trans-verse myelopathy. [8][9][10][11][12][13][14][15] Neuroradiological studies have shown an association between high intensity white matter lesions and the presence of aCL Ab, and some authors have suggested that aCL Ab are implicated in the pathogenesis of MS. However, others did not confirm that patients with MS and antiphospholipid antibodies constitute a subgroup of patients, which suggests that aCL Ab may be a non-specific marker of central nervous system injury.…”
mentioning
confidence: 99%
“…[5][6][7] There have been some case reports or series linking anticardiolipin antibodies (aCL Ab) and MS, optic neuritis, or trans-verse myelopathy. [8][9][10][11][12][13][14][15] Neuroradiological studies have shown an association between high intensity white matter lesions and the presence of aCL Ab, and some authors have suggested that aCL Ab are implicated in the pathogenesis of MS. However, others did not confirm that patients with MS and antiphospholipid antibodies constitute a subgroup of patients, which suggests that aCL Ab may be a non-specific marker of central nervous system injury.…”
mentioning
confidence: 99%
“…Involvement of the CNS is often reported in patients with primary antiphospholipid antibody syndrome (APLAS)14; focal infarcts are the commonest MRI abnormalities described in this disease, although brain atrophy and diffuse white matter hyperintense lesions can also be found in a high percentage of cases 815 16 Moreover, recent reports found that up to 20% of patients with MS with brain MRI findings highly suggestive for this disease16 17 can be consistently positive for antiphospholipid antibodies, thus suggesting a concomitant diagnosis of MS and APLAS.…”
mentioning
confidence: 99%
“…In contrast to Cuadrado's report, these patients frequently had antinuclear antibodies and low serum complement levels. Brain MRI studies could not distinguish one group from the other [71]. Tourbah and colleagues found no difference between patients with an aPL-associated MS-like illness and MS regarding age of onset, presenting symptoms and signs, neurological exam findings, or disease course.…”
Section: Transverse Myelopathy Optic Neuropathy and Multiple Sclerosismentioning
confidence: 94%